Stalin's last generation : Soviet post-war youth and the emergence of mature socialism - Fürst, Juliane 1973- (Oxford Univ. Press, 2010)
Marks and burns : youth and consequences of war -- Explaining the inexplicable : youth and post-war ideological campaigns -- Mechanisms of integration : rituals, icons, and idols -- Wartime heroes for post-war youth : the rise and fall of the young guard -- Morals under siege : the myth and reality of juvenile crime -- Redefining Sovietness : fashion, style, and nonconformity -- Comrades, friends, and lovers : post-war personal relations and gender identities in theory and practice -- Patterns of participation : finding a self in the system